Sacred Boundaries : Religious Coexistence and Conflict in Early-Modern France - Luria, Keith P. (Book collections on Project MUSE., 2005)
And the disciplinary approaches it employs - it will interest scholars in history, religion, anthropology, sociology, women's studies, and literary studies."--Jacket